Larangan Kawin Bagi Sampu Pisse Baja-Baja Dalam Masyarakat Adat Luwu di Kabupaten Luwu Propinsi Sulawesi Selatan = Marital Prohibition over Sampu Pisse Baja-Baja in Luwu Customary Society of Luwu Regency, ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This study aims to answer problems: sanction impotion on violation of stipulation of marital prohibition over sampu pisse baja-baja in Luwu custom-ary society